A systematic review of the effectiveness of game-based learning in English language teaching - Azzahra Fayoris Hafiza; Bambang Widi Pratolo (International Journal of Education and Learning, 2024)
The pedagogical approach of using educational games has been highly effective in instructing non-native English speakers with English as a second or foreign language. The researchers systematically analyze the effectiveness of game-based learning (GBL) in English language teaching (ELT) by identifying and analyzing the game genres used in English language learning and the learning outcomes achieved through GBL. Using a keyword search methodology in the ScienceDirect database, 17 relevant studies were analyzed. The findings indicate that various game genres, including interactive, role-play, memory, simulation, and strategy games, significantly enhance vocabulary, grammar understanding, and overall engagement in ELT. The study concludes that GBL is a highly effective approach in improving English language proficiency among non-native speakers.